1981
DOI: 10.1111/j.1523-536x.1981.tb01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Postpartum Care: Opportunities for Bonding, Reconstructing the Birth and Instruction

Abstract: The declining length of postpartum stay in hospitals has made it more difficult for staff to provide the kind of care recommended in the nursing literature. This study examines the association between satisfaction with care and three clinical procedures-parent-infant bonding, reconstructing birth events and instruction in care of self and baby.Data taken from an Arizona statewide survey of women who recently gave birth indicated little dissatisfaction with care. However, contingency table analysis revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The conclusions drawn from the analysis of data related to satisfaction with care make theoretical and practical sense and are consistent with the literature. Several researchers reported that satisfaction was related to participation in care (Davenport-Slack & Boylan, 1974; Humenick & Buegen, 1981;Kieffer, 1980;Sullivan & Beeman, 1981), birthing room environment (Schmidt, 1980), and nursing care (Schmidt, 1980;Shields, 1978). Maintenance of family integrity also was an important component of satisfaction (Kieffer, 1980;Scaer & Korte, 1978;Schmidt, 1980;Sullivan & Beeman, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusions drawn from the analysis of data related to satisfaction with care make theoretical and practical sense and are consistent with the literature. Several researchers reported that satisfaction was related to participation in care (Davenport-Slack & Boylan, 1974; Humenick & Buegen, 1981;Kieffer, 1980;Sullivan & Beeman, 1981), birthing room environment (Schmidt, 1980), and nursing care (Schmidt, 1980;Shields, 1978). Maintenance of family integrity also was an important component of satisfaction (Kieffer, 1980;Scaer & Korte, 1978;Schmidt, 1980;Sullivan & Beeman, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The one comparative study of an alternative in-hospital birth experience and conventional care did not examine satisfaction or the women's psychological experience although the better outcomes in the alternative group were attributed to women's "attitudes" (Goodlin, 1980). Studies reported in the literature (Davenport-Slack & Boylan, 1974;Humenick & Bugen, 1981;Scaer & Korte, 1978;Shields, 1978;Sullivan & Beeman, 1981) suggested that participation in care, quality nursing care, and family togetherness are associated with patient satisfaction. Likewise, two researchers (Kieffer, 1980;Schmidt, 1980) found similar factors influence patient satisfaction in their study of birthing rooms.…”
mentioning
confidence: 99%
“…The explanation as to why women in the two models differed on these items is unclear but may be related to an overall perception of quality and satisfaction The sixth and seventh items for which women differed between the groups were family involvement and adaptation of routines to their wishes; because both of these items are also strongly characteristic of FCPPC, the higher quality scores for the family-centered group was anticipated. Sullivan and Beeman (1981) also found that flexibility in routines resulted in higher satisfaction scores for postpartum women. In addition, they reported that over seventy percent of respondents wanted more involvement from significant others.…”
Section: Research Question 2: Are There Differences In Women's'-percementioning
confidence: 80%
“…First, Sullivan & Beeman (1981) examined the relationship between satisfaction of postpartum women and infant bonding. Only 57% were very satisfied.…”
Section: Women's Satisfaction With Postpartum Nursing Carementioning
confidence: 99%
See 1 more Smart Citation